Case Report: Hemophagocytic Lymphohistiocytosis and Non-Tuberculous Mycobacteriosis Caused by a Novel GATA2 Variant - Mika, Thomas; Vangala, Deepak; Eckhardt, Matthias; La Rosée, Paul; Lange, Christoph; Lehmberg, Kai; Wohlschläger, Charlotte; Biskup, Saskia; Fuchs, Ilka; Mann, Jasmin; Ehl, Stephan; Warnatz, Klaus; et al. (Frontiers in Immunology, 2021)
Hemophagocytic lymphohistiocytosis (HLH) is a disorder of uncontrolled immune activation with distinct clinical features including fever, cytopenia, splenomegaly, and sepsis-like symptoms. In a young adolescent patient a novel germline GATA2 variant (GATA2, c.177c>G; p.Tyr59*, heterozygous, likely pathogenic, NM_032638.4) was discovered and had resulted in non-tuberculous mycobacterial (NTM) infection and aggressive HLH. Strikingly, impaired degranulation of cytotoxic T-lymphocytes (CTL) and natural killer (NK)-cells was detected in CD107a-analyses. The affected patient was treated with HLA-matched unrelated alloHSCT, and subsequently all hematologic and infectious abnormalities including HLH and NTM resolved. This case supports early alloHSCT in GATA2 deficiencies as curative approach regardless of active NTM infection. Future studies on GATA2 c.177C>G; p.Tyr59* might help understanding its potential role in cytotoxic effector cell function and its contribution to HLH pathogenesis.